2014
DOI: 10.1097/jto.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 is Epigenetically Repressed in Human and Mouse Lung Tumors and Is Not Requisite for Survival of KRAS Mutant Lung Cancer

Abstract: Introduction GATA2 was recently described as a critical survival factor and therapeutic target for KRAS mutant non-small cell lung cancer (NSCLC). However, whether this role is affected by epigenetic repression of GATA2 in lung cancer is unclear. Methods GATA2 expression and promoter CpG island methylation were evaluated using human and mouse NSCLC cell lines and tumor-normal pairs. In vitro assays were used to study GATA2 repression on cell survival and during tobacco carcinogen-induced transformation. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Epigenetic regulation of these genes has been strongly implicated earlier in lung cancer. [37][38][39][40][41] However, methylation in genes such as CDKN2A did not cross the thresholds in our study possibly because differing methylation patterns in CDKN2A has been reported in different lung cancer histological types. 42 We detected smoking-related methylation changes in several CpGs or genes that have earlier been reported to associate with smoking.…”
Section: Discussionmentioning
confidence: 66%
“…Epigenetic regulation of these genes has been strongly implicated earlier in lung cancer. [37][38][39][40][41] However, methylation in genes such as CDKN2A did not cross the thresholds in our study possibly because differing methylation patterns in CDKN2A has been reported in different lung cancer histological types. 42 We detected smoking-related methylation changes in several CpGs or genes that have earlier been reported to associate with smoking.…”
Section: Discussionmentioning
confidence: 66%
“…S2B), suggest DNA methylation is likely involved in miR-486-5p repression. However, our HM450K-based quantitative methylation data [34,35] revealed that the ~5kb region containing miR-486 is strongly methylated in all samples including DNLT (Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
“…The methylation levels of ANK1B and ANK1E promoters in lung cancer were also quantified using our previous HM450K data [34,35]. A total of 18 HM450K probes interrogated the methylation levels of CpGs across the ANK1B and ANK1E promoters in NHBEC, DNLT (n=24), lung tumors (n=64), and Calu6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a multitude of studies have sought to define KRAS synthetic lethal genes (Costa-Cabral et al, 2016;Kim et al, 2013Kim et al, , 2016Luo et al, 2009;Scholl et al, 2009;Steckel et al, 2012), they have been notable for the fact that they hardly overlap, which has been attributed to the use of different cell lines and screening libraries that may suffer from off-target effects and partial knockdowns (Downward, 2015). As a result, many of the published synthetic lethal genes that have been explored independently have failed to reproduce (Fröhling and Scholl, 2011;Tessema et al, 2014). While a meta-analysis of published synthetic lethals could be an effective way to identify more robust candidates, a systematic integration and re-testing has not yet been performed (Christodoulou et al, 2017;Downward, 2015).…”
Section: Introductionmentioning
confidence: 99%